Factorial analysis of sports result components among the strongest speed skaters of the world at 500 meters distance - Morozova, E. A. (The Russian Journal of Physical Education and Sport, 2017)
Annotation. Modern tendencies in the sphere of speed skating are characterized by constant increase of speed of running at all competitive disciplines. Specialists in speed skating face the problem concerning methodical support of the training process among speed skaters: new tendencies demand new scientifically substantiated approaches to the training process organization, taking into account the specificity of competitive activity. Materials: The factors study, which determine the final result of speed skaters at 500 meters distance. In this article factorial analysis was used concerning the results of the V stage of the World Cup (2013) in Norway. Research methods: video of the heats and the official scoresheets of 18 strongest speed skaters-sprinters of the World were analyzed; statistical data handling was fulfilled with the help of STATGRAPHICS Centurion program; correlation matrix factorization was held with the help of principal components method. Results. At the first stage of factorial analysis fulfillment 10 factors were defined, which this or that way influence final results of speed skaters. At the second stage 4 key factors were revealed, which explain 83,91% of total sampling variance: the ability to develop maximum speed during the first and the second turns overcoming, the ability to hold gained speed during passing transitional line, the ability to fulfill the finishing break. The matrix of factorial loads analysis helped to reveal, that during 500 meters distance overcoming a speed skater gains maximum speed going out of the turn (at the distances of 150-200 m and 350-400 m). Conclusion. The final result of speed skaters at 500 meters distance mainly depends on the ability to develop maximum speed during a turn overcoming and on the ability to keep it while running straight; the starting length has less influence on the final result of a sportsman, than the mentioned above factors. During technical-tactical mastery improvement speed skaters should pay great attention to running along a turn as the most favorable length for maximum speed development.